La mayéutica en el desarrollo del pensamiento reflexivo, básica media, Escuela John F. Kennedy, Pasaje, 2023 - 2024. - Macas Tituana, Brigitte Mayelly; Armijos Torres, Juliana Mishell (Machala: Universidad Técnica de Machala, 2024)
The Socratic Method or Maieutics is an effective educational approach that utilizes questions and answers to challenge assumptions, expose contradictions, acquire knowledge, and encourages students to analyze, evaluate, and carefully reflect on the information presented to them. This method has positively contributed to enhancing writing skills, critical thinking abilities, and cognitive behavior. Furthermore, it also positively contributes to students' achievement and satisfaction in learning, and can be effectively used across all school disciplines. The foundation of this research is to provide reflection and critical thinking in individuals by helping them discover and develop their own knowledge through questioning and dialogue. Therefore, this thesis is focused on the impact of maieutics on the development of students' reflective thinking in the area of Social Studies in the middle school level of John F. Kennedy School in Pasaje, during the academic year 2023-2024, in order to address the identified issues. To carry out this research, a qualitative-quantitative methodology was used. The qualitative approach represents the characteristics observable in the studied phenomenon, which is maieutics for the development of reflective thinking. In contrast, the quantitative approach presents statistical data that allows quantifying the problem according to established indicators, thus determining the level of the problem obtained with the instrument responses. The techniques used in this research work include a survey administered to 112 students and interviews conducted with 4 middle school teachers. The data obtained indicate that 80 students at the middle school level possess a medium level of reflective thinking in the subject of Social Studies, while 22 students indicate a high level, and 10 students report a low level. This suggests that maieutics can contribute to improving their reflective skills such as thinking, discerning, and debating. Unfortunately, traditional methods continue to be applied, leading to a deficit in reasoning and self-criticism of their own learning.
El método Socrático o Mayéutica es un método educativo eficaz que utiliza preguntas y respuestas para desafiar suposiciones, exponer contradicciones, obtener conocimientos, anima a los estudiantes a analizar, evaluar y reflexionar detenidamente la información que se les transmite. Este método ha contribuido positivamente a mejorar las habilidades de escritura, las habilidades de pensamiento crítico y el comportamiento cognitivo. Además, también contribuye positivamente al logro y la satisfacción de los estudiantes en el aprendizaje, y puede utilizarse eficazmente en todas las disciplinas de la escuela. El fundamento de esta investigación es proveer la reflexión y el pensamiento crítico en los individuos ayudándoles a descubrir y desarrollar su propio conocimiento a través del cuestionamiento y el diálogo. Por lo tanto, la presente tesis está enfocada a incidir la mayéutica en el desarrollo del pensamiento reflexivo de los estudiantes en el área de Estudios Sociales de la básica media de la escuela John F. Kennedy de Pasaje, periodo lectivo 2023-2024 a fin de solucionar la problemática encontrada. Para llevar a cabo esta investigación, se utilizó la metodología cualicuantitativa, el enfoque cualitativo representa las características que pueden observarse en el fenómeno estudiado que es la mayéutica para el desarrollo del pensamiento reflexivo, en cambio, el enfoque cuantitativo plasma los datos estadísticos que permite cuantificar el problema según los indicadores establecidos, determinando así el nivel del problema obtenido con las respuestas de los instrumentos, de tal forma que, las técnicas utilizadas en el presente trabajo de investigación es la encuesta que se lo aplicó a 112 estudiantes y la entrevista a los 4 docentes de la básica media. Los datos que se obtuvieron señalan que, 80 estudiantes de la básica media poseen un nivel medio de pensamiento reflexivo en la asignatura de Estudios Sociales, por otro lado, 22 estudiantes indica que es alto, mientras que 10 estudiantes señalan que su nivel es bajo. Lo que indica que la mayéutica puede contribuir a mejorar sus habilidades reflexivas como pensar, discernir y debatir. Pero lamentablemente, se siguen aplicando métodos tradicionales lo que ocasiona el déficit de raciocinio y autocrítica de su propio aprendizaje.
Keywords: MAYEUTICA; APRENDIZAJE-ENSEÑANZA; PENSAMIENTO CRITICO; DOCENTE